Preclinical anti-cancer activity and multiple mechanisms of action of a cationic silver complex bearing N-heterocyclic carbene ligands - Allison, Simon J.; Sadiq, Maria; Baronou, Efstathia; Cooper, Patricia A.; Dunnill, Chris; Georgopoulos, Nikolaos T.; Latif, Ayşe; Shepherd, Samantha; Shnyder, Steve D.; Stratford, Ian J.; Wheelhouse, Richard T.; Willans, Charlotte E.; et al. (Cancer letters, 2017)
Organometallic complexes offer the prospect of targeting multiple pathways that are important in cancer biology. Here, the preclinical activity and mechanism(s) of action of a silver-bis(N-heterocyclic carbine) complex (Ag8) were evaluated. Ag8 induced DNA damage via several mechanisms including topoisomerase I/II and thioredoxin reductase inhibition and induction of reactive oxygen species. DNA damage induction was consistent with cytotoxicity observed against proliferating cells and Ag8 induced cell death by apoptosis. Ag8 also inhibited DNA repair enzyme PARP1, showed preferential activity against cisplatin resistant A2780 cells and potentiated the activity of temozolomide. Ag8 was substantially less active against non-proliferating non-cancer cells and selectively inhibited glycolysis in cancer cells. Ag8 also induced significant anti-tumour effects against cells implanted intraperitoneally in hollow fibres but lacked activity against hollow fibres implanted subcutaneously. Thus, Ag8 targets multiple pathways of importance in cancer biology, is less active against non-cancer cells and shows activity in vivo in a loco-regional setting. •Selective cytotoxic effects against cancer cells as opposed to non-cancer cells in vitro.•Lack of cross-resistance to cisplatin in vitro and pharmacological properties that are distinct from cisplatin.•Inhibition of multiple targets including (i) Thioredoxin reductase (Trx-R); (ii) PARP-1; (iii) topoisomerases I and II (with preferential inhibition of topoisomerase I); (iv) glycolysis.•In vivo activity against hollow fibres implanted intraperitoneally.